ANALISA STRATEGI BISNIS INDUSTRI PRINTER DALAM MENGHADAPI PASAR BEBAS - Novian Mardani (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2019)
The Electronic Industrial development growing up rapidly as world Industrial globalization. The electronic product which has high technology specially printer is as apart of electronic industry that has dynamic characteristic. Epson printer product sales in Indonesia shows as a leader in year 2005 as 37,26%. PT. IEI as company that producing printer has participated in development of electronic industry in Indonesia. Based on that fact so the research is done for mapping the company position in competition and resume the alternative strategy to strengthen the compete power. Analysis tool used to answer research goal is by using External Internal Matrix that has nine cells for identify company position and to choose alternative strategy and used SWOT analysis for completing company position. In defining company position is find out the rating, weight and score based on external factor evaluation and internal factor evaluation that has been filled by respondent. Respondent that choosen is manager level above due to they are more understand about the company. As result of analysis that score for External Factor Evaluation (EFE) is 3,09 and for Internal Factor Evaluation (IFE) is 3,06 so company position stated on cell II in condition of growth and build. For company alternative strategy from mapping result is market penetration, market development, product development and horizontal integration through mergered with competitor. Then company is recommended to do intensive strategy as market penetration, product development according to strength and weakness that they has.